Bigtech-Companies Ecosystems Prospects in the Payment Sector - D. А. Kochergin; E. S. Sheshukova (Финансы: теория и практика, 2022)
The relevance of the article is determined by solving the problems of expansion of BigTech-companies’ activities in the field of payments, which take place at present. The aim of the article to identify perspective directions of interaction of ecosystems with credit institutions in the payment sector. The authors used the following methods: system-functional, system-structural, statistical analysis and synthesis. The research analyzed current approaches to the definition of ecosystems and digital platforms and proposed the authorial interpretation; identified the main advantages associated with the participation of ecosystems in financial and payment intermediation; reviewed the models of provision of financial and payment services by ecosystems and identified the regulatory framework of their activities in foreign countries; proposed criteria for assigning a company to an ecosystem in Russia and marked out prospects of ecosystem activities in the payment sector. It is concluded that an ecosystem is a new institutional unit that has advantages in comparison with traditional financial institutions: the presence of a global customer base, the possibility of rapid implementation of network effects, the lack of excessive regulatory burden. Objective criteria that allow to assign a company to an ecosystem are: general and specific criteria that take into account the country characteristics of doing business, the level of development of the financial market, information technology, etc. Regulation of activities of ecosystems of the BigTech-companies allows to minimize basic, global and country risks by improving financial regulation and antimonopoly legislation, developing of unified standards and requirements for cross-border activities of ecosystems of BigTech-companies. The main scenarios of interaction between traditional financial institutions and ecosystems in the Russian financial and payment markets are: preservation of the dominance of traditional financial institutions; cooperation between banks and ecosystems; competition between banks and ecosystems; transition to a financial ecosystem dominance scenario.